We Have Been Believers : An African American Systematic Theology - Evans, James H., 1950- (Book collections on Project MUSE., 2012)
"Seeking to overcome the chasm between church practice and theological reflection, James H. Evans Jr., a major and distinctive voice in American religion, situates theology squarely in the nexus of faith with freedom. There, with a sure touch, he uplifts revelatory aspects of black religious experience that reanimate classical areas of theology, and he creates a theology with a heart, soul, and voice that speak directly to our condition. Edited and introduced by Stephen G. Ray Jr., the second edition, published on the twentieth anniversary of the first, includes three new essays that identify the value of the book for womanist, evangelical, and black church audiences. The new edition concludes with an Afterword by the author himself"--